Photochemistry of proteins and nucleic acids - McLaren, Arthur Douglas, 1917-1979; Shugar, D. (David) (International series of monographs on pure and applied biology. Division, Modern trends in physiological sciences., 1964)
Photochemistry of Proteins and Nucleic Acids deals with photobiology.